Bifunctional gallium cation chelators - A. G. Polivanova; I. N. Solovieva; D. O. Botev; D. Y. Yuriev; A. N. Mylnikova; M. S. Oshchepkov (Тонкие химические технологии)
Objectives. The chemistry of 67Ga and 68Ga radionuclides plays a key role in nuclear medicine for applications in radiopharmaceuticals, in particular, in noninvasive in vivo molecular imaging techniques. The use of radiometals for labeling biomolecules typically requires the use of bifunctional chelators, which contain a functional group for covalent bonding with the targeting vector in addition to the polydentate fragment coordinating the metal. The aim of the present review article is to analyze the currently accumulated experimental material on the development and application of bifunctional chelators of gallium cations in medical research, as well as to identify the main requirements for the structure of the chelator and its complexes with 68Ga, which are used to create effective Gabased pharmaceutical preparations.Results. The review analyzed macrocyclic bifunctional chelators forming stable in vivo complexes with 68Ga and acyclic chelators, whose main advantage is faster complexation kinetics due to the short half-life of 68Ga. The advantages and disadvantages of both types of ligands were evaluated. In addition, a critical analysis of the binding constants and the conditions for the formation of complexes was presented. Examples of the influence of the geometry, lipophilicity, and total charge of the metal complex on the biodistribution of target radiopharmaceuticals were also given.Conclusions. Despite the progress made in the considered areas of bifunctional chelators, the problem of correlating the chemical structure of a metal-based radiopharmaceutical with its behavior in vivo remains important. Comparative studies of drugs having an identical targeting vector but containing different bifunctional chelating agents could help further elucidate the effectof metal chelate moiety on pharmacokinetics. In order to create effective bifunctional chelating agents, it is necessary to take into account such factors as the stability and inertness of the chelator and its complexes under physiological conditions, lipophilicity, complexation kinetics, chelation selectivity, combinatoriality of the basic structure, along with economic aspects, e.g., the availability of raw materials and the complexity of the synthesis scheme.